Utilização de membrana de poliuretano para correção de manifestações patológicas causadas pela umidade - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
This paper dealt with the most common structural pathology found in reinforced concrete structures with the aim of analyzing them in relation to their causes and solving their possible treatment methods. The main objective of this work is to highlight the importance of preventing these discrepancies in order to avoid future problems, waste, rework and consequently additional costs in the budget. Another objective is to alert the reader to the severity and consequences that can occur as a result of negligence in the maintenance and correction of pathologies in reinforced concrete structures. First, the text presents what reinforced concrete is and then discusses the meaning of the word "pathology" and how they can be generated in reinforced concrete structures. The causes and mechanisms that can cause specific deterioration are also presented, in order to provide information on how to avoid pathologies that appear after consultation and elaboration of the implementation of pathological examination in the Edificio Residencial Salles, in Macapá - AP, diagnosing problems through visual inspection and design of appropriate interventions for each case, with proposed interventions and costs incurred by the proposed intervention. The implementation of the case study is an attempt to expand the existing evidence and thus expand the knowledge and development of building pathology. As methods, data obtained from a bibliographic survey was also used.
Keywords: Construção civil; Engenharia civil – patologia das estruturas; Inspeção predial; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS::ESTRUTURAS DE CONCRETO; ODS 9 – Indústria, inovação e infraestrutura; ODS 11 – Cidades e comunidades sustentáveis; ODS 12 – Consumo e produção responsáveis